An integrated approach to preventing cardiovascular disease: community-based approaches, health system initiatives, and public health policy - Tina Karwalajtys; Janusz Kaczorowski (Dove Medical Press, 2010)
Tina Karwalajtys1, Janusz Kaczorowski2,31Department of Family Medicine, McMaster University, Hamilton, ON, Canada; 2Primary Care & Community Research, Child & Family Research Institute, Vancouver, BC, Canada; 3Department of Family Practice, University of British Columbia, Vancouver, BC, CanadaAbstract: Cardiovascular disease (CVD) is largely the product of interactions among modifiable risk factors that are common in developed nations and increasingly of concern in developing countries. Hypertension is an important precursor to the development of CVD, and although detection and treatment rates have improved in recent years in some jurisdictions, effective strategies and policies supporting a shift in distribution of risk factors at the population level remain paramount. Challenges in managing cardiovascular health more effectively include factors at the patient, provider, and system level. Strategies to reduce hypertension and CVD should be population based, incorporate multilevel, multicomponent, and socioenvironmental approaches, and integrate community resources with public health and clinical care. There is an urgent need to improve monitoring and management of risk factors through community-wide, primary care-linked initiatives, increase the evidence base for community-based prevention strategies, further develop and evaluate promising program components, and develop new approaches to support healthy lifestyle behaviors in diverse age, socioeconomic, and ethnocultural groups. Policy and system changes are critical to reduce risk in populations, including legislation and public education to reduce dietary sodium and trans-fatty acids, food pricing policies, and changes to health care delivery systems to explicitly support prevention and management of CVD.Keywords: risk factors, blood pressure determination, community health services, community health planning, public health practice